Performance based planning in Queensland: A case of unintended plan-making outcomes. (January 2016) - Frew, Travis; Baker, Douglas; Donehue, Paul
Highlights: Planning in Queensland attempted to implement performance based planning. Uncertainty in plan making and performance standards made plans more inflexible and rigid. Poor state guidance in plan drafting resulted in hybridized plans that combined performance standards and prescriptive measures. Abstract: Performance based planning (PBP) is purported to be a viable alternative to traditional zoning. The implementation of PBP ranges between pure approaches that rely on predetermined quantifiable performance standards to determine land use suitability, and hybrid approaches that rely on a mix of activity based zones in addition to prescriptive and subjective standards. Jurisdictions in the USA, Australia and New Zealand have attempted this type of land use regulation with varying degrees of success. Despite the adoption of PBP legislation in these jurisdictions, this paper argues that a lack of extensive evaluation means that PBP is not well understood and the purported advantages of this type of planning are rarely achieved in practice. Few empirical studies have attempted to examine how PBP has been implemented in practice. In Queensland, Australia, the Integrated Planning Act 1997 (IPA) operated as Queensland's principal planning legislation between March 1998 and December 2009. While the IPA did not explicitly use the term performance based planning, the Queensland's planning system is widely considered to be performance based in practice. Significantly, the IPA prevented Local Government from prohibiting development or use and the term zone was absent from the legislation. How plan-making would be advanced under the new planning regime was not clear, and as a consequence local governments produced a variety of different plan-making approaches to comply with the new legislative regime. In order to analyse this variation the research has developed a performance adoption spectrum to classify plans ranging between pure and hybrid perspectives of PBP. The spectrum compares how land use was regulated in seventeen IPA plans 1 across Queensland. The research found that hybrid plans predominated, and that over time a greater reliance on risk adverse drafting approaches created a quasi-prohibition plan, the exact opposite of what was intended by the IPA. This paper concludes that the drafting of the IPA and absence of plan-making guidance contributed to lack of shared understanding about the intended direction of the new planning system and resulted in many administrative interpretations of the legislation. It was a planning direction that tried too hard to be different, and as a result created a perception of land use risk and uncertainty that caused a return to more prescriptive and inflexible plan-making methods.